Citizens’ sex offence myths and perceived effectiveness of sex offender community notification in South Korea - Chon, Donsoo (International journal of comparative and applied criminal justice, 2025)
Scholars have argued that myths about sex offences and offenders lead to support for sex offender community notification. However, studies on a direct association supporting this argument are scarce. This study therefore explored the relationship between citizens’ perceived sex offence myths and the perceived effectiveness of notification using a survey of more than 2,000 citizens in South Korea. The ordinal regression analysis suggests that citizens who support sex offence myths (e.g., sex offenders are likely to reoffend, target strangers, are mentally ill, or have no plan for sex offences) showed a high level of perceived effectiveness of notification (e.g., deterring sex offenders’ reoffending, deterring citizens’ sex offences, increasing public awareness of sex offences, and protecting children from sexual assaults). These findings imply that citizens need education about sex offence myths. Additionally, sex offender community notification should be used primarily for high-risk offenders.